Classic folk songs for kids [compact disc] : from Smithsonian Folkways. - Mitchell, Elizabeth, 1968-; Seeger, Pete, 1919-2014; Glazer, Tom; Leadbelly, 1885-1949; Jenkins, Ella; Guthrie, Sarah Lee; McGhee, Brownie, 1915-1996; Terry, Sonny; Lord Invader, 1914-1961; Ritchie, Jean; Paz, Suni; Houston, Cisco (Smithsonian Folkways, 2016)
With this collection, curator Jeff Place culls a cross-section of 26 classics from the Smithsonian Folkways vaults to tell an intriguing story of American signature sing-along. The songs' origins are as fascinating as the songs are fun: centuries-old European ballads, an American Revolutionary tune, Nineteenth-century American folksongs, African-derived game songs, a sea chantey, a railroad jingle, camp songs, and even an opera song.